2013
DOI: 10.1128/jcm.01096-13
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility Breakpoint for Enrofloxacin against Swine Salmonella spp

Abstract: Susceptibility breakpoints are crucial for prudent use of antimicrobials. This study has developed the first susceptibility breakpoint (MIC < 0.25 g/ml) for enrofloxacin against swine Salmonella spp. based on wild-type cutoff (CO WT ) and pharmacokinetic-pharmacodynamic (PK-PD) cutoff (CO PD ) values, consequently providing a criterion for susceptibility testing and clinical usage of enrofloxacin. Salmonella spp. are leading zoonosis and food-borne pathogens. Approximately 10 to 20% of all human cases of salmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
0
9
1
Order By: Relevance
“…To the best of our knowledge, this is the first study to establish the ECV and CO PD of DANO against E.coli by statistical method. The CO PD (0.03 μg/mL) was much lower than the ECV (8 μg/mL) established in our study, implying that the lower CO PD in our study may be due to the lower dose of drug administration to pigs, because previous studies concluded that the dose of drug administration may affect the PK-PD breakpoint [3638]. This suggests that (i) more dosing regimens need to be designed in future investigation; (ii) Further studies are needed to illustrate the relationship between DANO non-WT values proposed in this study and its resistant molecular mechanisms.…”
Section: Discussioncontrasting
confidence: 58%
“…To the best of our knowledge, this is the first study to establish the ECV and CO PD of DANO against E.coli by statistical method. The CO PD (0.03 μg/mL) was much lower than the ECV (8 μg/mL) established in our study, implying that the lower CO PD in our study may be due to the lower dose of drug administration to pigs, because previous studies concluded that the dose of drug administration may affect the PK-PD breakpoint [3638]. This suggests that (i) more dosing regimens need to be designed in future investigation; (ii) Further studies are needed to illustrate the relationship between DANO non-WT values proposed in this study and its resistant molecular mechanisms.…”
Section: Discussioncontrasting
confidence: 58%
“…The MIC 90 values of ENR against swine Camp. jejuni , Salmonella , E. coli , and Lawsonia intracellularis ( L. intracellularis ) that were collected from the literature are provided in Table 3 [ 10 , 11 , 55 , 56 , 57 ]. According to the predicted PK curve, the AUC 24h , C max , and T max of ENR in intestinal contents were 1065.23 μg h/mL, 201.07 μg/mL, and 1.0 h, respectively, at a dose of 5 mg/kg b.w.…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen different molecules of antibiotics belonging to nine classes were used for the MIC assay. The cutoff values recommended by CLSI (CLSI, 2016) except for enrofloxacin (Hao et al, 2013) and colistin (EUCAST, 2019) were used for the categorization of the results (Figure 1). The intermediate category was merged with the resistant ones for the analysis of our data.…”
Section: Methodsmentioning
confidence: 99%